Genesis of the essential characteristics of the “innovation activity” category - Maksiuta, A. (Ways to Improve Construction Efficiency, 2022)
The article analyzes scientific views on the definition of the meaning of the concepts of "innovation" and "innovative activity" by domestic and foreign scientists. The study of domestic and foreign economic literary sources showed that there is no unambiguous definition of the concepts of "innovation" and "innovative activity". The theoretical aspects of the development of innovation theory and its categorical apparatus are studied. Innovations at the current stage of economic development are the main means of maintaining the competitiveness of enterprises. Innovative activities of enterprises have a decisive influence on production, as innovations provide the maximum possible progressive influence on production. Increasing the efficiency of material production and ensuring the competitiveness of products is based on the use of new high-performance equipment and progressive technology, the use of modern organizational forms and economic management methods. Improvement of production is carried out on the basis of innovative activities at various stages of the "science-production" cycle. The innovative activity of the enterprise is a complex process of creation, use and distribution of innovations in order to obtain competitive advantages and increase the profitability of its production. In a market economy, the enterprise's innovative activity is the most essential factor that enables the enterprise to occupy a stable market position and gain an advantage over competitors in the field that is the sphere of its commercial interests. Based on the analysis, it was established that innovative activity is a set of activities (scientific, technological, production, organizational, financial and commercial) that collectively lead to innovation in the form of a new or improved product (service) or business technology.